Heterologous expression and purification of novel antimicrobial peptide Odorranain-F-OW1 in Escherichia coli forbiophysical characterisation - Divya Shet; D. Zarena (The Bioscan, 2026)
Small cationic peptides having microbicidal qualities are known as antimicrobial peptides, or AMPs. All living things, including humans, plants, and insects, create AMPs as a major component of their immediate, non-specific defenses against diseases. AMPs range in length from six to fifty amino acids. By specifically interacting with bacterial membranes, these peptides ultimately destroy the germs and provide the host with protection. Natural antimicrobial peptides are abundant in amphibian skin. Odorranain-F-OW1, a 29-residue frog peptide, was selected for the investigation from the AMP database (https://aps.unmc.edu/home) (2). To achieve soluble expression, the chosen peptide gene was cloned into the pET-32a(+) vector and fused with a thioredoxin tag. The E. Coli BL21 (DE3) strain's peptide was isolated for biophysical analysis after being expressed via induction. The E. Coli BL21 (DE3) strain's peptide was isolated for biophysical analysis after being expressed via induction. The antibacterial qualities of the peptide were validated by the disc diffusion method and agar well. Keywords Antimicrobial peptides, antibiotic-resistant bacteria, multidrug resistance (MDR), recombinant peptide, expression, fusion protein purification, CD, MALDI, NMR.